PALIPERIDONE ER: A NEW TREATMENT FOR SCHIZOPHRENIA - Dahlia Dahlia (Universitas Syiah Kuala, 2013)
Abstrak. Generasi kedua antipsikotik untuk pengobatan skizofrenia telah ditemukan. Paliperidone ER (Invega TM) telah disetujui pada tahun 2007 oleh Badan Pengawas Obat dan Makanan Amerika untuk mengobati pasien dengan skizofrenia. Formulasi Paliperidone ER yang munggunakan Alza OROS (Osmotic-controlled Release Oral-delivery System) dan menggunakan tekanan osmotic melepaskan pengobatan dalam tingkatan plasma darah yang ringan. Beberapa studi yang disponsori oleh Johnson dan Johnson Pharmaceutical Research and Development menemukan bahwa semua dosis Paliperidone ER efektif dalam mengontrol sejumlah besar simtom skizofrenia dan fungsi personal dan sosial pasien serta umumnya dapat ditoleransi dengan baik.Abstract. A new second-generation antipsychotic for the treatment of schizophrenia has been found. Paliperidone ER (Invega ™) was approved in 2007 by Food and Drug Administration (FDA) to treat patients with schizophrenia. The formulation of Paliperidone ER by using the Alza OROS (Osmotic-controlled Release Oral-delivery System) and utilizing osmotic pressure release medication in smooth blood plasma levels. Several studies that were sponsored by Johnson and Johnson Pharmaceutical Research and Development found that all doses of paliperidone ER is effective in controlling a broad range of the symptoms of schizophrenia and personal and social functioning and generally well tolerated.